Frequency Domain Long-Term Prediction for Low Delay General Audio Coding - Guo, Ning; Edler, Bernd (IEEE Signal Processing Letters, 2021)
In this paper we propose a long-term prediction method for low delay transform domain general audio coders. This Frequency Domain Joint Harmonics Prediction (FDJHP) method operates directly in the Modified Discrete Cosine Transform (MDCT) domain and can enhance the coding efficiency, even under very low frequency resolutions. We compare this new method with state-of-the-art MDCT based methods by analyzing bitrate savings and by a listening test using test signals with strong harmonic components. The results indicate that it outperforms an existing method, which also directly operates in the frequency domain. Additionally, we show how it can be combined with the existing techniques into an adaptive system, where the different methods can complement each other.<br

Frequency Domain Prediction of Tonal Signals with Time-Varying Pitches - Guo, Ning; Edler, Bernd (IEEE Signal Processing Letters, 2024)
In this paper we propose an Extended Frequency Domain Joint Harmonics Prediction (EFDJHP) algorithm, which does long term prediction directly in the transform domain on tonal signals with time-varying pitches for transform speech and audio coding. EFDJHP is an algorithm extension of a previously proposed Frequency Domain Joint Harmonics Prediction (FDJHP) algorithm where a constant pitch between neighboring frames was assumed [1]. A linearly changing pitch between adjacent frames is assumed in EFDJHP, where the linearity can be assumed to be local and updated across frames. EFDJHP works in a backward prediction fashion without additional algorithmic delay, and needs very few side information for the forward adaption of the predictor coefficients. Bitrate saving analysis and a listening test show that EFDJHP can improve the coding efficiency on tonal signals with frequent pitch variations such as singing voices and speech.
CRIS-Team Scopus Importer:2024-11-22
Keywords: audio coding; FDJHP; Long Term Prediction; time varying pitch